Studying the Causality Relationship between Inflation and Money Supply in the Libyan Economy Using Tod -Yamamomoto's Methodology - Alderdeer, Abdulhakam; Mansour, Abdulbasit O. (Journal of Pure & Applied Sciences, 2022)
Using the methodology of standard strings analysis this paper examined and analyzed the relationship between money supply and inflation in the Libyan economy, during the period 198-2018; to reach this goal, the stationary of the two variables of the study was tested using the unit root test that was reached by the Extended Dickey - Fuller method, then a cointegration test.  With the Angel-Granger methodology to test the relationship in the long run, then these tests were supplemented with the causation test, as it consisted of the Granger test in the short term and Toda-Yamamomoto's choice of causation in the long term;  The results showed that each of the study variables stabilized after taking the first difference for them, while the results of the causation test for Granger showed a circular relationship between the two variables in the short term, meaning that each variable causes the other, while the Toda-Yamamomoto causality test in the long term showed no  A causal relationship between the two variables, none of which causes the other.     The study recommends that the money supply management and the monetary authorities in Libya should manage the money supply in a practical way based on research papers that contribute to clarifying the relationship between money supply and inflation.  Which would contribute to making correct decisions.